2019
DOI: 10.2136/sssaj2018.10.0405
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐Gas Diffusivity and Soil‐Moisture effects on N2O Emissions from Intact Pasture Soils

Abstract: Grazed pastures are recognized as a dominant source of nitrous oxide (N2O), a highly potent greenhouse gas. Studies have examined soil physical controls on N2O emissions, including soil moisture status. Limited attempts to link N2O emissions with soil‐diffusivity (Dp/Do), using repacked soil cores, have shown peak N2O emissions to align with a relatively narrow window of Dp/Do, despite a relatively wide range in water‐filled pore space (WFPS), across a range of soil bulk densities. Such detailed studies have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…Diffusivity is mainly controlled by soil bulk density and water saturation (Balaine et al, 2013;Klefoth et al, 2014). These empirical models predict diffusivity based on empirical relationships with total porosity ( ) and air-filled porosity (ε) (Millington and Quirk, 1961;Moldrup et al, 2000;Resurreccion et al, 2010;Deepagoda et al, 2011Deepagoda et al, , 2019. As expected the discrepancy between calculated D emp and simulated D sim was highest at water saturation > 75 % WFPS, where discontinuity due to packing procedure took full effect as described earlier (Figs.…”
Section: How To Substitute Microscale Information By Bulk Propertiessupporting
confidence: 63%
See 1 more Smart Citation
“…Diffusivity is mainly controlled by soil bulk density and water saturation (Balaine et al, 2013;Klefoth et al, 2014). These empirical models predict diffusivity based on empirical relationships with total porosity ( ) and air-filled porosity (ε) (Millington and Quirk, 1961;Moldrup et al, 2000;Resurreccion et al, 2010;Deepagoda et al, 2011Deepagoda et al, , 2019. As expected the discrepancy between calculated D emp and simulated D sim was highest at water saturation > 75 % WFPS, where discontinuity due to packing procedure took full effect as described earlier (Figs.…”
Section: How To Substitute Microscale Information By Bulk Propertiessupporting
confidence: 63%
“…The dependence of denitrification on diffusion constraints was demonstrated by several models that were developed to predict the formation of anoxic centres within soil aggregates (Greenwood, 1961;Arah and Smith, 1989;Arah and Vinten, 1995;Kremen et al, 2005). The distance threshold for anoxic conditions to emerge was set on an ad hoc basis at 5 mm from connected air at the end of incubation but is likely to vary with O 2 demand by local microbial activity (CO 2 release represented by the green fringe area, item 2) during the incubation (Kremen et al, 2005;Rabot et al, 2015;Ebrahimi and Or, 2018;Keiluweit et al, 2018;Kravchenko et al, 2018;Schlüter et al, 2019). Because we could only conduct X-ray CT scans at the end of incubation, redistribution of water during the incubation time cannot be ruled out.…”
Section: Which Processes Govern Denitrification In Soil?mentioning
confidence: 99%
“…Balaine et al [20] showed that relative gas diffusivity (D p /D o ; where D p is the soil gas diffusion coefficient (m 3 soil air m −1 soil s −1 ) and D o is the gas diffusion coefficient in free air (m 2 air s −1 )) was better than WFPS for identifying the threshold of N 2 O production when comparing soils across a range of bulk densities and soil moistures. This was further confirmed using repacked soil cores, intact soil cores and in situ [21][22][23]. A D p /D o value ≤ 0.02 indicates the onset of anaerobic soil conditions [24], while a value of 0.006 has been shown to result in peak N 2 O emissions [20].…”
Section: Introductionmentioning
confidence: 77%
“…Balaine et al, 2013;Owens et al, 2017), thus recognizing the potential of D p /D o as a key predictor for soil conditions that are conducive for N 2 O fluxes. Recent studies have also indicated the presence of a critical diffusivity window (D p /D o ∼ 0.005-0.01), in both intact and repacked pasture soils, which yields a peak in N 2 O emissions regardless of the soil texture, structure, and soil moisture status (Chamindu Deepagoda et al, 2019). Calculation of D p /D o essentially requires solving the classical Fick's laws of diffusion under specified boundary conditions.…”
Section: Core Ideasmentioning
confidence: 99%